Computational Methods in Multiphase Flow VII 2013
DOI: 10.2495/mpf130061
|View full text |Cite
|
Sign up to set email alerts
|

Air-water two-phase flow through U-bend, sudden expansion and sudden contraction in rectangular mini-channels

Abstract: The evaluation of pressure loss in gas-liquid two-phase flow through singularities is important for designing compact heat exchangers such as cooling devices in electronic equipment. However, the accurate evaluation methods are scarce especially for mini-channel flow. In the present study, air-water twophase flow and water single-phase flow experiments were conducted at room temperature using three kinds of horizontal rectangular mini-channels each with a U-bend, sudden expansion, and sudden contraction. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Sadatomi et al [3] investigated flow regime, pressure drop, bubble velocity and void fraction for air-water two phase flow through U-bend, sudden expansion and sudden contraction in rectangular minichannel. Kusumaningsih et al [5] conducted experimental investigations on nitrogen gasliquid (distilled water, ethanol 49 wt% aqueous solution, pure ethanol and HFE 7200) two-phase flows in two kinds of rectangular microchannels with the widths of in the larger channels upstream of the contraction 0.53 or 0.78 mm (0.240 mm in height), while 0.240 mm (0.240 mm in height) the smaller ones.…”
Section: Department Of Mechanical System Engineering Graduate Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…Sadatomi et al [3] investigated flow regime, pressure drop, bubble velocity and void fraction for air-water two phase flow through U-bend, sudden expansion and sudden contraction in rectangular minichannel. Kusumaningsih et al [5] conducted experimental investigations on nitrogen gasliquid (distilled water, ethanol 49 wt% aqueous solution, pure ethanol and HFE 7200) two-phase flows in two kinds of rectangular microchannels with the widths of in the larger channels upstream of the contraction 0.53 or 0.78 mm (0.240 mm in height), while 0.240 mm (0.240 mm in height) the smaller ones.…”
Section: Department Of Mechanical System Engineering Graduate Schoolmentioning
confidence: 99%
“…In particular, the small and narrow channels are widely adopted in compact heat exchangers [2]. Recently, such a flow through singularity in micro and minichannels ranged from 100 μm to 10 mm becomes popular because compact heat exchangers with phase change, such as cooling devices of electronic equipment and refrigerators, are miniaturized [3].…”
Section: Introductionmentioning
confidence: 99%
“…Usui et al have studied possible flow patterns occurring at different velocities of gas and liquid and their mutual transformation while passing through a return U bend. Later, several researchers proposed different correlations for the calculation of pressure drop along U bends considering different fluid combinations. Sadatomi et al carried out experiments for different flow rates of air–water and observed their effect along a channel with a U bend, a sudden contraction and expansion. Yadav and Mehta have explained the effect of the radius of curvature of a U bend on the flow patterns and the hydrodynamics behind the Taylor bubble flow.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researches have been reported on two-phase flows in small channel with singularities. Among them, Sadatomi et al [2] investigated flow regime, pressure drop, bubble velocity and void fraction for air-water two phase flow through U-bend, sudden expansion and sudden contraction in rectangular minichannel. Kawahara et al [3] conducted experimental investigations on gas-liquid two-phase flows in two kinds of rectangular microchannels with the width of in the larger channels upstream from the contraction were 0.53 or 0.78 mm at 0.230 mm in height, while that in the smaller ones was 0.270 mm at 0.230 mm in height.…”
Section: Introductionmentioning
confidence: 99%